A Preclinical Evaluation of Antimycin A as a Potential Antilung Cancer Stem Cell Agent. (12th June 2013) - Yeh, Chi-Tai; Su, Chun-Li; Huang, Chi-Ying F.; Lin, Justin Kung-Yi; Lee, Wei-Hwa; Chang, Peter M.-H.; Kuo, Yu-Lun; Liu, Yu-Wen; Wang, Liang-Shun; Wu, Chih-Hsiung; Shieh, Yi-Shing; Jan, Yi-Hua; et al.
Abstract : Drug resistance and tumor recurrence are major obstacles in treating lung cancer patients. Accumulating evidence considers lung cancer stem cells (CSCs) as the major contributor to these clinical challenges. Agents that can target lung CSCs could potentially provide a more effective treatment than traditional chemotherapy. Here, we utilized the side-population (SP) method to isolate lung CSCs from A549 and PC-9 cell lines. Subsequently, a high throughput platform, connectivity maps (CMAPs), was used to identify potential anti-CSC agents. An antibiotic, antimycin A (AMA), was identified as a top candidate. SP A549 cells exhibited an elevated stemness profile, including Nanog, β -catenin, Sox2, and CD133, and increased self-renewal ability. AMA treatment was found to suppress β -catenin signaling components and tumor sphere formation. Furthermore, AMA treatment decreased the proliferation of gefitinib-resistant PC-9/GR cells and percentage of SP population. AMA demonstrated synergistic suppression of PC-9/GR cell viability when combined with gefitinib. Finally, AMA treatment suppressed tumorigenesis in mice inoculated with A549 SP cells. Collectively, we have identified AMA using CMAP as a novel antilung CSC agent, which acts to downregulate β -catenin signaling. The combination of AMA and targeted therapeutic agents could be considered for overcoming drug resistance and relapse in lung cancer patients.